2011
DOI: 10.1103/physrevlett.107.223001
|View full text |Cite
|
Sign up to set email alerts
|

Realization of an Optomechanical Interface Between Ultracold Atoms and a Membrane

Abstract: We have realized a hybrid optomechanical system by coupling ultracold atoms to a micromechanical membrane. The atoms are trapped in an optical lattice, which is formed by retroreflection of a laser beam from the membrane surface. In this setup, the lattice laser light mediates an optomechanical coupling between membrane vibrations and atomic center-of-mass motion. We observe both the effect of the membrane vibrations onto the atoms as well as the backaction of the atomic motion onto the membrane. By coupling t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
219
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(222 citation statements)
references
References 31 publications
3
219
0
Order By: Relevance
“…An alternate line of research has been pursued in circuit and cavity optomechanics [15], where the position of a mechanical oscillator is coupled to the frequency of a high-Q electromagnetic resonance allowing for backaction cooling [16,17] and continuous position readout of the oscillator. Such optomechanical resonators have long been pursued as quantum-limited sensors of weak classical forces [9,15,[18][19][20], with more recent studies exploring optomechanical systems as quantum optical memories and amplifiers [21][22][23][24], quantum nonlinear dynamical elements [25], and quantum interfaces in hybrid quantum systems [26][27][28][29].Despite the major advances in circuit and cavity optomechanical systems made in the last few years, all experiments to date involving the cooling of mesoscopic mechanical oscillators have relied on careful measurement and calibration of the motion-induced scattering of light to obtain the average phonon occupancy of the oscillator, hni. Approach towards the quantum ground state in such experiments is manifest only as a weaker measured signal, with no evident demarcation between the classical and quantum regimes of the oscillator.…”
mentioning
confidence: 99%
“…An alternate line of research has been pursued in circuit and cavity optomechanics [15], where the position of a mechanical oscillator is coupled to the frequency of a high-Q electromagnetic resonance allowing for backaction cooling [16,17] and continuous position readout of the oscillator. Such optomechanical resonators have long been pursued as quantum-limited sensors of weak classical forces [9,15,[18][19][20], with more recent studies exploring optomechanical systems as quantum optical memories and amplifiers [21][22][23][24], quantum nonlinear dynamical elements [25], and quantum interfaces in hybrid quantum systems [26][27][28][29].Despite the major advances in circuit and cavity optomechanical systems made in the last few years, all experiments to date involving the cooling of mesoscopic mechanical oscillators have relied on careful measurement and calibration of the motion-induced scattering of light to obtain the average phonon occupancy of the oscillator, hni. Approach towards the quantum ground state in such experiments is manifest only as a weaker measured signal, with no evident demarcation between the classical and quantum regimes of the oscillator.…”
mentioning
confidence: 99%
“…In a proof-of-principle experiment, we have observed the backaction of the atoms onto the membrane oscillator, as reported in Ref. [27]. The present article reviews these experiments, including a more detailed theoretical description of our system and a discussion of the conditions required to observe normal mode splitting.…”
Section: Introductionmentioning
confidence: 91%
“…It has been demonstrated that a large radiation pressure can be generated in the cavity that in return may lead to entanglement between different components of the system. In particular, stationary entanglement has been predicted between the cavity mode and a vibrating mirror [5][6][7][8][9], between an atomic ensemble or a Bose-Einstein condensate located inside an optical cavity and the vibrating mirror of the cavity [10][11][12][13], between two vibrating mirrors of a ring cavity [14], between two dielectric membranes suspended inside a cavity [15], and between a membrane and a trapped atom both located inside a cavity [16][17][18]. Further studies have addressed interesting problems of entangling mechanical oscillators [19], entangling optical and microwave cavity modes [20], and the creation of a photon by a vibrating mirror [21].…”
Section: Introductionmentioning
confidence: 99%